Agente de combate às endemias no processo de trabalho da equipe de saúde da família - Oliveira, Marcelo Marques (2013)
The aim of this study was to inclusion the activities of Agents to Combat Endemic Diseases (ACE) in the process of work of Family Health teams (SF), from the reports of their activities with the families and teams for a municipality of Minas Gerais. This is a descriptive and cross-sectional study. The study included 57 ACE, who answered a questionnaire itself, self-administered, consisting of closed and open questions. It was found that 81% are female, 72% with age below 40 years, 72% had completed high school, and all had less than six years of experience working as ACE. Regarding the number of buildings 61.5% of ACE has under its responsibility a total of 800 to 1000 buildings, being that 95% carry out daily more than 31 visits to homes. It was observed that 51% of ACE did not attend the Foundation Course training, but 86% reported participation in training courses during the work sponsored by the Municipal. 88% reported not being well received by the family in the home visits. In the work of teams of SF process, activities are not just an individual, it is collective, joint and complementary activities. We concluded that the actions of ACE in work of teams of SF become complex, since it involves his training, preparation for the activities, in addition to the organization and management of services. Although feel integrated with the team, it was observed that in weekly meetings of the team, more than 50% of ACE reported not having space to submit the results of their actions. Information and knowledge needs of families seized by them during home visits or informally, an object of the work process, were not valued by the team. Changing the health care of people, replacing the conventional practices of care implies to new work process and requires greater dedication women's long-vent training tank top to the members and families. The movement of recognition and appreciation of these actors would need to be mobilised, because the incorporation of ACE in the teams of SF shows potential for health care in an integral way and participation of families in resolvability of health problems and health promotion. Keywords: health care, health promotion, family health program.